Social aspects of care - Coyle, Nessa (HPNA palliative nursing manuals ;, 2016)
'Social Aspects of Care' provides an overview of financial and mental stress illness places, not just on the patient, but on the family as well. This volume contains information on how to support families in palliative care, cultural considerations important in end-of-life care, sexuality and the impact of illness, planning for the actual death, and bereavement.